Peningkatan Hasil Belajar Pendidikan Agama Katolik Melalui PBL Bermedia Powerpoint pada Fase C Kelas V Materi Perempuan dan Laki-Laki Saling Melengkapi di SD Xaverius Lubuk Linggau - Ely Retnowati (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
Education is a fundamental pillar in nation-building, and continuous efforts are required to enhance the quality of education. The Merdeka Curriculum, implemented in Indonesia, includes Catholic Religious Education and Character Education. However, SD Xaverius Lubuklinggau faces challenges in improving students' learning outcomes in these subjects, particularly in Phase C of Grade V in the Science Program. The issues are related to character and academic achievements. This research proposes a solution by implementing the Problem-Based Learning (PBL) model assisted by powerpoint media. The aim of the study is to evaluate the improvement of students' learning outcomes in the aspects of faithful character and academic achievement. Through classroom action research with two cycles using tests and observations as data collection techniques, the results indicate that the PBL model assisted by powerpoint media is effective in enhancing students' learning outcomes With a focus on the material that women and men complement each other, this research contributes to a deeper understanding of how innovative approaches can improve the quality of education, particularly in the context of Catholic Religious Education and Character Education at SD Xaverius Lubuklinggau.